Septic cardiomyopathy: Diagnosis and management - Florence Boissier; Nadia Aïssaoui (2021)
There is an extensive body of literature focused on sepsis-induced myocardial dysfunction, but results are conflicting and no objective definition of septic cardiomyopathy (SCM) has been established. SCM may be defined as a sepsis-associated acute syndrome of non-ischemic cardiac dysfunction with systolic and/or diastolic left ventricular (LV) dysfunction and/or right ventricular dysfunction. Physicians should consider this diagnosis in patients with sepsis-associated organ dysfunction, and particularly in cases of septic shock that require vasopressors. Echocardiography is currently the gold standard for diagnosis of SCM. Left ventricular ejection fraction is the most common parameter used to describe LV function in the literature, but its dependence on loading conditions, particularly afterload, limits its use as a measure of intrinsic myocardial contractility. Therefore, repeated echocardiography evaluation is mandatory. Evaluation of global longitudinal strain (GLS) may be more sensitive and specific for SCM than LV ejection fraction (LVEF). Standard management includes etiological treatment, adapted fluid resuscitation, use of vasopressors, and monitoring. Use of inotropes remains uncertain, and heart rate control could be an option in some patients.